I Know Why I Choose Private Label Brands - Brand Equity Analysis in Organized Retailing - Ravi, Shilpa Sarvani; Ram Prasad, M. V. (Indian Journal of Marketing, 2020)
Private label brands (PLB), also referred to as ’store brands,’ are termed to be saviors of the organized retail stores. As the retail revolution is taking place in India, consumers are finding private label products to be high-quality items that offer them a smart way to save money. Retailers see them as a way to improve their financial performance and create consistent store traffic. As both sides place more and more value on private labels, PLBs are fuelling the growth options for the retailers. The present study analyzed the brand equity of PLBs by identifying exclusive 23 various factors underlying brand equity preferences by the consumers. This study elaborated the major reasons behind the consumersâ€™ preference of PLBs over the national brands. This study examined 407 respondents from East and South Bangalore city. Furthermore, the study analyzed significance of each factor - Brand Association, Perceived Value, Brand Loyalty, Perceived Quality, Perceived Risk, and Brand Awareness in consideration of the Aakerâ€™s model of brand equity. The interpretation was conducted by analyzing each factor impacting brand equity of PLBs using factor analysis. The regression results strongly articulated that Perceived Quality and Store Associations were the major factors influencing brand equity.